2020
DOI: 10.1093/nar/gkaa462
|View full text |Cite
|
Sign up to set email alerts
|

The role of 3′UTR-protein complexes in the regulation of protein multifunctionality and subcellular localization

Abstract: Abstract Multifunctional proteins often perform their different functions when localized in different subcellular compartments. However, the mechanisms leading to their localization are largely unknown. Recently, 3′UTRs were found to regulate the cellular localization of newly synthesized proteins through the formation of 3′UTR-protein complexes. Here, we investigate the formation of 3′UTR-protein complexes involving multifunctional proteins by exploiting large-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
(104 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, some of these proteins lack a localization signal but are known to localize in the plasma membrane. The authors proposed that in the absence of any conventional localization signals, these multiple 3 0 -UTRprotein complexes might have a role in a more common but not yet disclosed protein trafficking mechanism (Ribeiro et al, 2020).…”
Section: Alternative 3 0 -Utrs Determine Protein Function and Subcellular Localizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, some of these proteins lack a localization signal but are known to localize in the plasma membrane. The authors proposed that in the absence of any conventional localization signals, these multiple 3 0 -UTRprotein complexes might have a role in a more common but not yet disclosed protein trafficking mechanism (Ribeiro et al, 2020).…”
Section: Alternative 3 0 -Utrs Determine Protein Function and Subcellular Localizationmentioning
confidence: 99%
“…A bioinformatics search for protein complexes mediated by the 3 0 -UTR using human extreme multifunctional (EMF) proteins as a model revealed that 128 EMF proteins may form thousands of 3 0 -UTR-protein complexes (Ribeiro et al, 2020). Interestingly, some of these proteins lack a localization signal but are known to localize in the plasma membrane.…”
Section: Alternative 3 0 -Utrs Determine Protein Function and Subcell...mentioning
confidence: 99%
“… 33 A recent study indicates that the 3’UTR region of genes can influence mRNA location and protein abundance through their effects on mRNA stability and translation. 34 Ribeiro et al 35 revealed that genetic information stored in gene 3’UTR can affect protein expression through protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, RBP binding to 3′UTRs on nascent transcripts regulates poly(A) signal site selection, cleavage, and polyadenylation (e.g., review: Tian & Manley, 2013). On mature transcripts, 3′UTRs contain interaction sites (originally termed “zip‐code” motifs [Kislauskis & Singer, 1992; Kislauskis et al., 1994; Ross et al., 1997]), for subcellular trafficking (Arora et al., 2022; Kim et al., 2015; Ribeiro et al., 2020; Yergert et al., 2021) anchoring points for scaffolding interactions (Sahoo et al., 2018) and interaction sites for recruitment of miRNAs (Grimson et al., 2007; Majoros & Ohler, 2007) or inhibition by competition for binding sites (Srikantan et al., 2012).…”
Section: Introductionmentioning
confidence: 99%